2014
DOI: 10.1002/ejoc.201403195
|View full text |Cite
|
Sign up to set email alerts
|

Desulfitative C‐Arylation of Glycals by Using Benzenesulfonyl Chlorides

Abstract: The palladium‐catalyzed stereoselective synthesis of 2,3‐deoxy‐C‐aryl glycosides was investigated. The strategy is based on the Pd‐catalyzed desulfitative Heck coupling of arylsulfonyl chlorides and glycals with good leaving groups. An attempt was made to establish the reaction mechanism, which may involve PdII/Pd0 interconversion under basic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…(Scheme b) . Related results reported by Mukherjee et al demonstrated the application of the Pd‐catalysed desulfitative coupling of sulfonyl chlorides in processes yielding the same type of products …”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…(Scheme b) . Related results reported by Mukherjee et al demonstrated the application of the Pd‐catalysed desulfitative coupling of sulfonyl chlorides in processes yielding the same type of products …”
Section: Introductionmentioning
confidence: 70%
“…[35] Related results reported by Mukherjee et al demonstrated the application of the Pd-catalysed desulfitative coupling of sulfonyl chlorides in processes yielding the same type of products. [30] The open chain trans alkenes are also possible outcomes of the glycal transformations as demonstrated by Ye et al in Hecktype reactions carried out with Ni-catalyst and boronic acids as the reactant (Scheme 1c). [29] An additional work describing formation of the open chain products in the reaction of glycals and terminal alkynes under metal-free conditions has been reported recently expanding further synthetic potential of these carbohydrate derivatives (Scheme 1d).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This method provides a straightforward access to the halo-substituted β-aryl ketones 79 in moderate to good yields, as they demonstrated the compatibility of this reaction with iodo-and bromo-functionalities on the benzenesulfinate. 76 Their strategy was based on use of OAc as leaving group. The use of 10 mol% PdCl 2 (PPh 3 ) 2 catalyst, Li 2 CO 3 base in dioxane at 140 °C was found to be the optimal conditions.…”
Section: Heck Type Reactionmentioning
confidence: 99%